A study on Optimal Resource Allocation Policy in Cloud Environment - Archana Naik, Kavitha Sooda, KarunakarRai (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the role of the resource allocator, the characteristics that are taken into account while allocating resources and the resource allocation mechanisms. The cloud computing enables the utility-based resource allocation to the customers. The resource allocation mechanism needs to consider the better utilization of the resources and the minimized cost per service to the customer. These condition for resource allocation expects the resource allocation to be viewed as the optimization problem. To perform the optimized allocation, the allocator must be equipped with the status of the resources, predicted demand from the customers, and dynamic changes in the cloud. In this work, we have categorized the parameters for the resource allocator based on the cost of allocation, utilization of the resources, time taken to execute and reliability. An architecture for the resource allocator is proposed considering the service level agreement, the user request, and the resource status. A framework to build the resource allocator model is proposed.